Usefulness of semi-solid medical foods administered after percutaneous endoscopic gastrostomy - Yusaku Kajihara (The Indonesian Society for Digestive Endoscopy, 2021)
Background: Even if preoperative enteral nutrition is administered without any issues, some patients suffer from gastrointestinal symptoms (e.g., vomiting and diarrhea) after initiating gastrostomy feeding. Because of the amino acid composition and limited amount of lipids, elemental diets may reduce the risk of gastrointestinal symptoms. However, elemental diets are expensive. Semi-solid medical foods are inexpensive and more closely mimic normal physiology than elemental diets. The aim of the present study was to investigate the usefulness of semi-solid medical foods when administered after percutaneous endoscopic gastrostomy (PEG).Method: This retrospective study analyzed 91 patients who had PEG performed by the author who was the attending physician. All patients received preoperative enteral nutrition with liquid nutrients, and there were no instances of gastrointestinal symptoms before PEG tube placement. The types of nutrients administered after PEG were divided into three categories: semi-solid medical foods (n = 20), polymeric formulas (n = 26), and elemental diets (n = 45). The incidence of gastrointestinal symptoms was compared among the three groups.Results: No gastrointestinal symptoms occurred in the semi-solid medical foods group; the incidence of gastrointestinal symptoms in the semi-solid medical foods group was significantly lower than that of the polymeric formulas group [0% vs. 26.9% (7/26), p 0.05] and was similar to that of the elemental diets group [0% vs. 2.2% (1/45), p = 1].Conclusion: If preoperative enteral nutrition is administered without any issues, semi-solid medical foods are useful as nutrients administered after PEG tube placement.